DEVELOPMENT OF LIBRARY MARKETING IN THE CONTEXT OF DIGITAL TRANSFORMATION - Yakubbayeva, E’zozxon (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article analyzes the role and significance of marketing activities in the field of library science from a scientific and analytical perspective. It examines the transformation of library activities in the modern information society, user-oriented services, digital marketing, and management based on statistical analysis. The study also identifies existing problems in library marketing and proposes scientifically grounded solutions.